Phonecards produced in honor of the 35th anniversary of the Institute of Technology in Immunobiologicals and the centenary of the Ezequiel Dias Foundation - Wagner de Souza Tavares (Cadernos Cajuína)
The telecommunications company Oi S.A. issued phonecards printed with images of important Brazilian institutions. The aim, of this study, was to identify, describe and discuss the context in which the phonecards of the Institute of Technology in Immunobiologicals (Bio-Manguinhos) and the Ezequiel Dias Foundation (FUNED) were issued. The Bio-Manguinhos card was issued in honor of the institution’s 35th anniversary and is printed with an image of the building facade, while the FUNED card was issued in honor of its centenary and is printed with an image of the building where the auditorium and library are located. The cards were presented at ceremonies attended by authorities and represented the beginning of their circulation in Brazil. These cards could be used by the general public in payphones for telephone services. Making them available to the general public in the Brazilian states where Oi S.A. operated and circulating the cards among card vendors and collectors paid homage to and publicized the work carried out by these institutions among the Brazilian population and even abroad.